Award ceremony BIGSAS honorary doctorate for Dr. Fatou Sow (2022)
On 18 May the University of Bayreuth will festively present Dr. Fatou Sow with the BIGSAS Honorary Doctorate. With this award, the Senegalese sociologist Dr. Fatou Sow – based at the Cheikh Anta Diop University in Dakar and the Centre National de la Recherche Scientifique (CNRS) in Paris – is recognised for her unwavering commitment to the cause of women and her outstanding scholarly achievements in feminist topics on the African continent. Sow is a veritable pioneer of gender studies and African feminism, who has worked at the forefront of women’s rights in West Africa and beyond for more than half a century. The award was first announced during her keynote lecture at the Africa Multiple Cluster of Excellence conference on 14 July 2021 and will now be festively celebrated on 18 May this year. The ceremony will take place on campus, however may also be attended online. Please register for either event format by visiting https://bigsas-award-ceremony.wr-events.de/